2018
DOI: 10.17235/reed.2018.5644/2018
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a percutaneous cholecystostomy catheter in situ until the time of cholecystectomy on the development of recurrent acute cholecystitis: a historical cohort study

Abstract: maintaining percutaneous cholecystostomy tubes in place until the time of surgery in surgically fit patients may help to prevent a recurrence after acute calculous cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
2
8
0
1
Order By: Relevance
“…In our case, the surgeon on call decided for a temporizing solution to solve the acute condition before de nitive surgery. This choice is supported by several studies suggesting that PC followed by late laparoscopic cholecystectomy is a suitable management for patients with ACC deemed un t for emergency surgery (9,31,32). In a paper of 2016, Popowicz et al, (32) reviewed the medical reports of seven hospitals with 799 pts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, the surgeon on call decided for a temporizing solution to solve the acute condition before de nitive surgery. This choice is supported by several studies suggesting that PC followed by late laparoscopic cholecystectomy is a suitable management for patients with ACC deemed un t for emergency surgery (9,31,32). In a paper of 2016, Popowicz et al, (32) reviewed the medical reports of seven hospitals with 799 pts.…”
Section: Discussionmentioning
confidence: 99%
“…(Table1) Also Wang et al, in another paper, suggested keeping the PC tube in place until cholecystectomy in critically ill patients. However, some other studies report adverse events, one of them (9) indicating that a drainage duration longer than two weeks may be associated with increased recurrence. Other policies have been catheter removal after con rmation of the patency of the cystic duct (8) or until surgery (10,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Also the optimal duration of PC drainage, as reported in a paper by Hasbahceci et al is still a controversial issue [8]. The suggested time is considered to be three to six weeks, with an average of one month, but Morse et al recommended that the PC tube should remain in place in critically ill patients until cholecystectomy (Table 1) [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to clarify the timing of PC tube removal before definitive surgery. Furthermore, recurrence after catheter removal is an important issue in patients not undergoing surgical treatment [6,8,11]. [3,4,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of an SMC without a guidewire access is feasible and safe [9,10]. Additionally, the extra-vascular use of an SMC to navigate difficult obstructions shows promise for patients with obstructive renal calculi, or in this case, cholelithiasis [9].…”
Section: Discussionmentioning
confidence: 99%